Ionizing radiation interaction with charged graphene: An experimental evaluation attempt. (September 2020) - Fornalski, Krzysztof W.; Adamowski, Łukasz; Bonczyk, Michał; Winkowska-Struzik, Magdalena
Abstract: The experimental evaluation of photon radiation interaction with charged material was undertaken. Gamma and X-ray radiation was directed at graphene deposited on copper foil with a constant electrostatic charge. The radiation counter measured changes in the radiation intensity after passing the graphenous slab. It was confirmed that additional charge can increase the total cross section of photon interaction with matter, and the relative reduction of radiation intensity by (0.42 ± 0.15)% per 10 -5  C/cm 2 on the single slab proved that it is possible to construct thin and lightweight radiation shields. This result is important for radiation protection during deep space travel, for example. Highlights: Experimental evaluation of X-ray interaction with charged material was undertaken. The tested material was the flake graphene deposited on copper foil. Additional electric charge can increase the cross section of photon interaction. This confirms the effect which was postulated theoretically two years earlier. This result is important e.g. for radiation protection during deep space travel.